Digital Land Transformation : Optimizing the Issuance of Electronic Land Certificates by BPN Gorontalo City - Seldi Munandar; Weny Almoravid Dungga; Zamroni Abdussamad (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the optimization of the issuance of electronic land certificates in Gorontalo City and find out the efforts of the government (BPN) Gorontalo City in optimizing the issuance of electronic land certificates. This type of research is empirical legal research. This method involves a juridical sociological approach, namely an approach that starts from existing legal rules or norms and then harmonizes with the reality that exists in society. The results of this study indicate that the issuance of electronic land certificates (E-Certificate) in Gorontalo city is considered not optimal. Researchers found that there are 3 out of 4 indicators that have not been maximized in its implementation, namely the readiness of land office infrastructure, policy implementation, and public understanding. Furthermore, the efforts that have been made by BPN Gorontalo City in optimizing the issuance of electronic land certificates are conducting Socialization and Education to the Public, Improving Information Technology Infrastructure, Cooperation with Stakeholders, Increasing Human Resources Capacity and Resolving Obstacles and Constraints.